Is the maternal health voucher scheme associated with increasing routine immunization coverage? Experience from Bangladesh - Sultana, Nazia; Hossain, Aazia; Das, Hemel; Pallikadavath, Saseendran; Koeryaman, Mira; Rahman, Mohammad; Chowdhury, Asiful Haidar; Bhuiya, Abbas; Mahmood, Shehrin Shaila; Hanifi, S. M. A. (Frontiers in Public Health, 2023)
Bangladesh initiated the maternal health voucher scheme (MHVS) in 2007 to increase maternal and child health practices and bring equity to the mainstream of health systems by reducing financial and institutional barriers. In this study, we investigated whether the MHVS has an association with immunisation coverage in a rural area of Bangladesh. Between 30 October 2016 and 15 June 2017, we carried out a cross sectional survey in two low performing area in terms of immunization coverage- Chattogram and Sylhet division of Bangladesh. We calculated the coverage of fully immunised children (FIC) for 1151 children aged 12 to 23 months of age. We compared the coverage of FIC between children whose mothers enrolled in MHVS and children whose mother did not. We analysed immunisation coverage using the crude odds ratio (OR) and adjusted OR (aOR) from binary logistic regression models. One-fifth mothers enrolled for the MHVS. The overall coverage of FIC was 86%. Ninety-three percent children whose mothers were MHVS members were fully immunised whereas the percentage is 84% for the children of the mothers who were not enrolled in MHVS. Multivariate analysis also shows the fact that FIC coverage was higher for children whose mothers enrolled in MHVS compared to those children whose mothers did not; the aOR was 2.03 (95% confidence interval 1.11-3.71). Maternal health voucher scheme (MHVS) provides a window for non-targeted benefits of childhood vaccination. Providing health education to pregnant mothers during prenatal care may motivate them to immunise their children. Programmes targeted for mothers during pregnancy, childbirth and post-natal may further increase the utilisation of priority health services such as childhood immunisation.